Photocatalytic Water‐Splitting Coupled with Alkanol Oxidation for Selective N‐alkylation Reactions over Carbon Nitride. Issue 2 (27th November 2020) - Xu, Yangsen; Zhang, Zhaofei; Qiu, Chuntian; Chen, Shaoqin; Ling, Xiang; Su, Chenliang
Abstract: Photocatalytic water splitting technology (PWST) enables the direct use of water as appealing "liquid hydrogen source" for transfer hydrogenation reactions. Currently, the development of PWST‐based transfer hydrogenations is still in an embryonic stage. Previous reports generally centered on the rational utilization of the in situ generated H‐source (electrons) for hydrogenations, in which photogenerated holes were quenched by sacrificial reagents. Herein, the fully‐utilization of the liquid H‐source and holes during water splitting is presented for photo‐reductive N ‐alkylation of nitro‐aromatic compounds. In this integrate system, H‐species in situ generated from water splitting were designed for nitroarenes reduction to produce amines, while alkanols were oxidized by holes for cascade alkylating of anilines as well as the generated secondary amines. More than 50 examples achieved with a broad range scope validate the universal applicability of this mild and sustainable coupling approach. The synthetic utility of this protocol was further demonstrated by the synthesis of existing pharmaceuticals via selective N ‐alkylation of amines. This strategy based on the sustainable water splitting technology highlights a significant and promising route for selective synthesis of valuable N ‐alkylated fine chemicals and pharmaceuticals from nitroarenes and amines with water and alkanols. Abstract : Nothing left to waste : Full utilization of the liquid H‐source and holes during water splitting was realized for selective N ‐alkylation of nitro‐aromatic compounds, including pharmaceuticals, under visible light with high selectivity, good functional group tolerance, and wide reaction scope.